Photocurable composition for imprinting

The yield and heat resistance of high Abbe number and low birefringent materials in the prior art are solved by using photocurable compositions composed of silica particles modified by ethylenically unsaturated functional groups and other ethylenically unsaturated compounds. The efficiency of optical characteristics and stability of the anti-reflection layer are achieved.

CN112292749BActive Publication Date: 2024-12-31NISSAN CHEM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980042208.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-06-27
Filing Date
2019-05-28
Publication Date
2024-12-31
Estimated Expiration
2039-05-28

AI Technical Summary

Technical Problem

It is difficult to develop photocurable resin materials with high ABB number and low birefringence, and its anti-reflection layer is prone to cracks after heat treatment, affecting the heat resistance and yield of the lens.

Method used

Using a photocurable composition composed of silica particles having ethylenically unsaturated functional groups, an ethylenically unsaturated monofunctional acrylate compound, an ethylenically unsaturated polyrothane and a photo-radical initiator, by Combination and treatment methods of specific proportions form cured substances with high refractive index and low birefractive index, and an anti-reflective layer is formed on the film formation to avoid cracks.

Benefits of technology

The optical characteristics of high ABB number, high refractive index and low birefractive are achieved. The anti-reflection layer does not produce cracks after heat treatment, and it is not easy to produce cracks in the development process, which improves the heat resistance and yield of the lens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002852839750000201
    Figure BDA0002852839750000201
  • Figure BDA0002852839750000231
    Figure BDA0002852839750000231
  • Figure BDA0002852839750000241
    Figure BDA0002852839750000241
Patent Text Reader

Abstract

The subject of the present invention is to provide a new photocurable composition for imprinting. The solution is a photocurable composition for imprinting, which is a photocurable composition for imprinting comprising the following (a) component, the following (b) component, the following (c) component, and the following (d) component, wherein, relative to 100 parts by weight of the total amount of compounds having ethylenically unsaturated groups contained in the composition, the (a) component is 10 to 40 parts by weight, the (b) component is 10 to 50 parts by weight, the (c) component is 1 to 10 parts by weight, and the (d) component is 0.1 to 5 parts by weight. (a): silica particles having a primary particle size of 1 nm to 100 nm and surface-modified with functional groups having ethylenically unsaturated groups (b): monofunctional (meth)acrylate compound having ethylenically unsaturated groups (c): polyrotaxane having ethylenically unsaturated groups (d): photoradical initiator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photocurable composition for imprinting, comprising silica particles whose surface is modified with a functional group having an ethylenically unsaturated group, a monofunctional (meth)acrylate compound having an ethylenically unsaturated group, a polyrotaxane having an ethylenically unsaturated group, and a photoradical initiator. Specifically, the present invention relates to a photocurable composition having excellent optical properties (high refractive index, high Abbe number, low birefringence), wherein an antireflection layer (AR layer) is formed on the upper layer of a cured product and a molded product, and the antireflection layer does not crack even after heat treatment, and further, the cured product does not crack even after washing or development using an organic solvent. Background Art

[0002] Resin lenses are used in electronic devices such as mobile phones, digital cameras, and car cameras, and are required to have excellent optical properties corresponding to the purpose of the electronic device. In addition, depending on the form of use, high durability such as heat resistance and weather resistance, as well as high productivity that can be molded with a good yield rate are required. As materials for resin lenses that meet such requirements, thermoplastic transparent resins such as polycarbonate resins, cycloolefin polymers, and methacrylic resins are used.

[0003] In addition, multiple lenses are used in high-resolution camera modules, but lenses with low wavelength dispersion, that is, lenses with high Abbe numbers, are mainly used, and optical materials for forming them are required. Furthermore, in order to improve the yield and production efficiency when manufacturing resin lenses and further suppress the optical axis deviation when the lenses are stacked, the transition from injection molding of thermoplastic resins to wafer-level molding by press molding using curable resins that are liquid at room temperature is actively studied. For wafer-level molding, from the perspective of productivity, it is generally a hybrid lens method in which lenses are formed on a support such as a glass substrate.

[0004] As a photocurable resin capable of wafer-level molding, in the past, a free radical curable resin composition was used from the viewpoints of high transparency, heat yellowing resistance, and mold release properties (Patent Document 1). In the case where the molded body is a lens, an anti-reflection layer formed of inorganic substances such as silicon oxide and titanium oxide is formed on the upper layer. Therefore, there is a problem of generating cracks in the anti-reflection layer by heat-treating the lens covered with the anti-reflection layer.

[0005] In addition, curable compositions containing surface-modified oxide particles such as silica particles surface-modified with a silane compound and zirconium oxide particles surface-modified with a dispersant are known to obtain a cured product having a high Abbe number (for example, Patent Documents 2 and 3). In a development step in which an uncured portion such as the outer periphery of a wafer-shaped molded body on which a plurality of lens patterns are formed after imprinting is washed with an organic solvent, the organic solvent significantly erodes the wafer-shaped molded body, thereby causing cracks in the wafer-shaped molded body.

[0006] Furthermore, regarding a cured product formed from a general free radical curable resin composition, stress due to curing shrinkage accumulates in the cured product, causing birefringence. If a cured product with high birefringence is used as a lens for a high-pixel camera module, the resulting image will be distorted, so a curable resin composition for a lens is required to have low birefringence.

[0007] On the other hand, it is known that there are cyclic molecules, linear molecules, and blocking groups (stoppers) with openings, and the blocking groups are arranged at both ends of a pseudopolyrotaxane that is enclosed by the linear molecule in the opening of the cyclic molecule to form a string, and the cyclic molecule has a polyrotaxane of (meth) acryloyl group (for example, patent document 4). The above-mentioned linear molecules penetrate the opening of the above-mentioned cyclic molecules, and the above-mentioned blocking groups are arranged in a manner that the cyclic molecules do not detach from the linear molecules. In addition, the so-called "inclusion" refers to the introduction of other molecules into the space of the opening of the cyclic molecule, and the so-called "pseudopolyrotaxane" refers to a polyrotaxane that does not have the above-mentioned blocking groups. The photocurable composition containing the above-mentioned polyrotaxane can produce a photocured material with high strength, high elastic modulus, and excellent toughness.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 5281710 (International Publication No. 2011 / 105473)

[0011] Patent Document 2: Japanese Patent Application Publication No. 2014-234458

[0012] Patent Document 3: International Publication No. 2016 / 104039

[0013] Patent Document 4: International Publication No. 2016 / 072356 Summary of the invention

[0014] Problems to be solved by the invention

[0015] There is no molded body having a high Abbe number (e.g., 53 or more) and low birefringence, which can be used as a lens for a high-resolution camera module, and in which an antireflection layer formed on the upper layer of the molded body does not crack due to a subsequent heat treatment, and further, a curable resin material that does not crack the wafer-shaped molded body in a development step of washing the uncured portion such as the outer periphery of the above-mentioned wafer-shaped molded body with an organic solvent, and development thereof is desired. The present invention is made in view of such circumstances, and its subject is to provide a photocurable composition that can form a molded body showing a high Abbe number, a high refractive index and low birefringence, and can form a molded body having a high crack resistance that does not cause cracks in the antireflection layer on the upper layer due to heat treatment of the molded body and does not cause cracks even when exposed to a development step.

[0016] Methods for solving problems

[0017] A first embodiment of the present invention is a photocurable composition for imprinting, comprising the following component (a), the following component (b), the following component (c), and the following component (d), wherein the amount of the component (a) is 10 to 40 parts by mass, the amount of the component (b) is 10 to 50 parts by mass, the amount of the component (c) is 1 to 10 parts by mass, and the amount of the component (d) is 0.1 to 5 parts by mass, relative to 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition.

[0018] Component (a): Silica particles having a primary particle size of 1 nm to 100 nm and surface-modified with a functional group having an ethylenically unsaturated group

[0019] Component (b): Monofunctional (meth)acrylate compound having an ethylenically unsaturated group

[0020] Component (c): Polyrotaxane having an ethylenically unsaturated group

[0021] (d) Ingredient: Photoradical initiator

[0022] The imprint photocurable composition of the present invention may further contain 5 to 50 parts by mass of the component (e) and / or the component (f) described below, based on 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition.

[0023] Component (e): a polyfunctional (meth)acrylate compound having an ethylenically unsaturated group and not containing an aromatic ring (wherein component (e) does not include the polyrotaxane as component (c) and the urethane (meth)acrylate compound or epoxy (meth)acrylate compound as component (f).

[0024] Component (f): a urethane (meth)acrylate compound or an epoxy (meth)acrylate compound having an ethylenically unsaturated group (however, component (f) does not include the polyrotaxane as component (c) above.)

[0025] The imprint photocurable composition of the present invention may further contain 0.05 to 3 parts by mass of the following component (g) relative to 100 parts by mass of the total amount of the compounds having an ethylenically unsaturated group contained in the composition, and / or 0.1 to 3 parts by mass of the following component (h) relative to 100 parts by mass of the total amount of the compounds having an ethylenically unsaturated group contained in the composition.

[0026] (g) Ingredients: Phenolic antioxidants

[0027] (h) ingredient: thioether antioxidant

[0028] The silica particles surface-modified with a functional group having an ethylenically unsaturated group of the component (a) are, for example, silica particles surface-modified with a (meth)acryloyloxy group bonded to a silicon atom via a divalent linking group, for example, an alkylene group having 1 to 5 carbon atoms, preferably an alkylene group having 2 or 3 carbon atoms.

[0029] The polyfunctional (meth)acrylate compound not containing an aromatic ring as the component (e) may be composed of two or more compounds. In this case, at least one of the two or more compounds has an alicyclic hydrocarbon group.

[0030] The refractive index n of the cured product of the above-mentioned imprint photocurable composition at a wavelength of 589 nm is D is 1.49 or more, and the Abbe number ν of the cured product is D The refractive index n is greater than 53. D 、The above Abbe number ν D The higher the value, the better. For example, as long as the refractive index n D is greater than or equal to 1.49 and less than or equal to 1.55, and the Abbe number ν D The range may be 53 or more and 60 or less.

[0031] A second aspect of the present invention is a cured product of the above-mentioned photocurable composition for imprint.

[0032] A third aspect of the present invention is a method for producing a resin lens, comprising the step of imprint molding the above-mentioned imprint photocurable composition.

[0033] The fourth embodiment of the present invention is a method for producing a molded body, which is a method for producing a molded body of a photocurable composition for imprint, comprising the following steps: a step of filling the space between a support and a casting mold that are in contact with each other, or the internal space of a detachable casting mold with the photocurable composition for imprint; and a step of exposing the photocurable composition for imprint filled in the space to photocuring. The casting mold is also called a mold.

[0034] The method for producing a molded article of the present invention may further include the following steps: after the above-mentioned photocuring step, taking out the obtained photocured article and demolding the article; and heating the photocured article before, during or after the demolding step.

[0035] After the mold releasing step and before the heating step, a developing step using an organic solvent may be further included.

[0036] In the method for producing a molded article of the present invention, the molded article is, for example, a lens for a camera module.

[0037] Effects of the Invention

[0038] The photocurable composition for imprinting of the present invention comprises the above-mentioned components (a) to (d), and further arbitrarily comprises the above-mentioned components (e) and / or the above-mentioned components (f), and the above-mentioned components (g) and / or the above-mentioned components (h). Therefore, the cured product and molded body obtained from the photocurable composition show the desired optical properties as an optical device, for example, a lens for a high-resolution camera module, i.e., a high Abbe number, a high refractive index and a low birefringence. In addition, with respect to the cured product and molded body obtained from the photocurable composition of the present invention, the anti-reflection layer of the upper layer of the cured product and the molded body does not produce cracks or wrinkles even after heat treatment at 175°C, and further does not produce cracks in the development process using an organic solvent. DETAILED DESCRIPTION

[0039] The components of the imprint photocurable composition of the present invention are described in more detail. In addition, in the present invention, the so-called ethylenically unsaturated group includes a group having a double bond between two carbon atoms, for example, a (CH2=CH)- group and a [CH2=C(CH3)]- group. The compounds having an ethylenically unsaturated group contained in the imprint photocurable composition of the present invention are components (a) to (c), and these components also correspond to the case where the composition contains at least one of the above-mentioned components (e) and (f).

[0040] [Component (a): Silica particles whose surface is modified with a functional group having an ethylenically unsaturated group]

[0041] The primary particle size of the silica particles surface-modified with functional groups having ethylenically unsaturated groups that can be used as the (a) component of the photocurable composition for imprinting of the present invention is 1 nm to 100 nm. Here, the so-called primary particles are particles that constitute the powder, and the particles formed by agglomerating the primary particles are called secondary particles. The above-mentioned primary particle size can be calculated from the relationship between the specific surface area (surface area per unit mass) S of the above-mentioned silica particles surface-modified with functional groups having ethylenically unsaturated groups measured by the gas adsorption method (BET method), the density ρ of the surface-modified silica particles, and the primary particle size D: D=6 / (ρS). The primary particle size calculated by this relationship is the average particle size, which is the diameter of the primary particles. In addition, the above-mentioned silica particles surface-modified with functional groups having ethylenically unsaturated groups are surface-modified with, for example, (meth)acryloyloxy groups bonded to silicon atoms via divalent linking groups. When using the silica particles surface-modified with the functional group having an ethylenically unsaturated group, the surface-modified silica particles may be used directly, or a colloidal substance obtained by pre-dispersing the surface-modified silica particles in an organic solvent as a dispersion medium (a sol in which colloidal particles are dispersed in a dispersion medium) may be used. When using a sol containing the surface-modified silica particles, a sol having a solid content concentration in the range of 10% to 60% by mass may be used.

[0042] As the sol containing the silica particles whose surfaces are modified with the functional groups having ethylenically unsaturated groups, for example, MEK-AC-2140Z, MEK-AC-4130Y, MEK-AC-5140Z, PGM-AC-2140Y, PGM-AC-4130Y, MIBK-AC-2140Z, MIBK-SD-L (all manufactured by Nissan Chemical Industries, Ltd.), and ELCOM (registered trademark) V-8802, ELCOM V-8804 (all manufactured by JGC Catalysts & Chemicals Co., Ltd.) can be used.

[0043] The content of the component (a) of the imprint photocurable composition of the present invention is 10 to 40 parts by mass, preferably 15 to 35 parts by mass, relative to 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition. If the content of the component (a) is less than 10 parts by mass, cracks in the antireflection layer formed on the upper layer of the cured product and the molded body obtained from the imprint photocurable composition may not be suppressed, and if it is more than 40 parts by mass, the cured product and the molded body may generate haze, and the transmittance may be reduced.

[0044] The silica particles whose surfaces are modified with a functional group having an ethylenically unsaturated group as the component (a) may be used alone or in combination of two or more.

[0045] [Component (b): Monofunctional (meth)acrylate compound having an ethylenically unsaturated group]

[0046] The monofunctional (meth)acrylate compound having an ethylenically unsaturated group that can be used as the component (b) of the imprint photocurable composition of the present invention is a compound having one (meth)acryloyloxy group in one molecule of the compound. Examples of the monofunctional (meth)acrylate compound include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, and the like. Acrylate, menthyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, 2-methyladamantan-2-yl (meth)acrylate, 2-ethyladamantan-2-yl (meth)acrylate, tricyclo[5.2.1.0(2,6)]decyl (meth)acrylate, tricyclo[5.2.1.0(2,6)]decyloxyethyl (meth)acrylate. Among them, from the viewpoint of refractive index, it is preferred to use an alicyclic (meth)acrylate compound having an alicyclic structure.

[0047] As the monofunctional (meth)acrylate compound having an ethylenically unsaturated group, commercially available products can be used, for example, Bisoncoat #155, IBXA, ADMA (all manufactured by Osaka Organic Chemical Industry Co., Ltd.), NK Ester A-IB, NK Ester IB, AS, S, S-1800A, A-1800M (all manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), and Fancleil (registered trademark) FA-511AS, Fancleil FA-512AS, Fancleil FA-513AS, Fancleil FA-512M, Fancleil FA-512MT, Fancleil FA-513M (all manufactured by Hitachi Chemical Co., Ltd.).

[0048] The content of the component (b) of the imprint photocurable composition of the present invention is 10 to 50 parts by mass, preferably 20 to 45 parts by mass, relative to 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition. If the content of the component (b) is less than 10 parts by mass, the effect of reducing the birefringence of the cured product and the molded body obtained from the imprint photocurable composition may become insufficient, and if it is more than 50 parts by mass, the crosslinking density of the cured product and the molded body may decrease, and the shape of the cured product and the molded body may be deformed during heat treatment.

[0049] The monofunctional (meth)acrylate compound having an ethylenically unsaturated group as the component (b) may be used alone or in combination of two or more.

[0050] [Component (c): polyrotaxane having an ethylenically unsaturated group]

[0051] The polyrotaxane having an ethylenically unsaturated group that can be used as the component (c) of the imprint photocurable composition of the present invention has a cyclic molecule having an ethylenically unsaturated group, and a blocking group is arranged at both ends of the pseudo-polyrotaxane that is enclosed by a linear molecule at the opening of the cyclic molecule so that the cyclic molecule does not separate. The cyclic molecule, the linear molecule, and the blocking group, which are the constituent elements of the polyrotaxane having an ethylenically unsaturated group in the cyclic molecule, are described.

[0052] <c-1. Cyclic molecules>

[0053] The cyclic molecule of the polyrotaxane with ethylenically unsaturated groups of component (c) is not particularly limited as long as it is cyclic and has an opening, and is encapsulated by a straight-chain molecule to form a string. The constituent element of the polyrotaxane with ethylenically unsaturated groups is preferably a cyclic molecule, and the ethylenically unsaturated groups can be directly combined with the cyclic molecules or combined via a spacer. As the spacer, there is no particular limitation, and for example, alkylene, alkyleneoxy, hydroxyalkylene, carbamoyl, acrylate chain, polyalkylene ether chain, and polyalkylene carbonate chain can be cited. As the above-mentioned cyclic molecule, it is preferably selected from, for example, α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.

[0054] <c-2. Straight-chain molecules>

[0055] The linear molecule of the polyrotaxane having an ethylenically unsaturated group of the component (c) is not particularly limited as long as it can be included in the opening of the cyclic molecule used in a string-like manner. For example, as the linear molecule, the compounds (polymers) exemplified in Patent Document 4 can be cited, among which a polymer selected from polyethylene glycol, polyisoprene, polyisobutylene, polybutadiene, polypropylene glycol, polytetrahydrofuran, polydimethylsiloxane, polyethylene, polypropylene, polyvinyl alcohol and polyvinyl methyl ether is preferred, and polyethylene glycol is particularly preferred.

[0056] The weight average molecular weight of the linear molecule is 1,000 or more, preferably 3,000 to 100,000, and more preferably 6,000 to 50,000. In the polyrotaxane having an ethylenically unsaturated group as component (c), the combination of (cyclic molecule, linear molecule) is preferably (derived from α-cyclodextrin, derived from polyethylene glycol).

[0057] <c-3. Blocking group>

[0058] The blocking group of the polyrotaxane with an ethylenically unsaturated group of component (c) is not particularly limited as long as it is a group that is disposed at both ends of the pseudopolyrotaxane and acts in a manner that the cyclic molecule used does not dissociate. For example, as a blocking group, the blocking groups exemplified in Patent Document 4 can be cited, among which, preferably, a blocking group selected from dinitrophenyl, cyclodextrin, adamantyl, trityl, fluorescein, silsesquioxane, and pyrene, more preferably adamantyl or cyclodextrin. The blocking group is, for example, bonded to the above-mentioned linear molecule via a -NH-C(=O)- group.

[0059] As the above-mentioned polyrotaxane having an ethylenically unsaturated group, a commercially available product can be used, and examples thereof include Seruman (registered trademark) Seroton.ーポリマーSA1303P, セルムスーパーポリマーSA2403P, セルムスーパーポリマーS A3403P、セルムスーパーポリマーSM1303P、セルムスーパーポリマーSM2403 P. Semantec 3403P (above, manufactured by Semantec Co., Ltd.).

[0060] The content of the component (c) of the imprint photocurable composition of the present invention is 1 to 10 parts by mass, preferably 3 to 7 parts by mass, relative to 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition. If the content of the component (c) is less than 1 part by mass, the effect of suppressing the generation of cracks in the cured product in the development process using an organic solvent may become insufficient, and if it is more than 10 parts by mass, the shape change of the cured product and the molded body during heating may increase due to the low elastic modulus.

[0061] The polyrotaxane having an ethylenically unsaturated group as the component (c) may be used alone or in combination of two or more.

[0062] [Component (d): Photoradical initiator]

[0063] Examples of the photoradical initiator that can be used as the component (d) of the photocurable imprint composition of the present invention include alkyl phenones, benzophenones, Michler's ketones, acylphosphine oxides, benzoylbenzoates, oxime esters, tetramethylthiuram monosulfide and thioxanthones, and photocleavage-type photoradical polymerization initiators are particularly preferred. As the photoradical initiator, commercially available products can be used, for example, IRGACURE (registered trademark) 184, IRGACURE 369, IRGACURE 651, IRGACURE 500, IRGACURE 819, IRGACURE 907, IRGACURE 784, IRGACURE 2959, IRGACURE CGI1700, IRGACURE CGI1750, IRGACURE CGI1850, IRGACURE CG24-61, IRGACURE TPO, IRGACURE 1116, IRGACURE 1173 (all manufactured by BASF Japan Co., Ltd.), ESACURE KIP150, ESACURE KIP65LT, ESACURE KIP100F, ESACURE KT37, ESACURE KT55, ESACURE KTO46, ESACURE KIP75 (above, manufactured by Lamberti).

[0064] The content of the component (d) of the imprint photocurable composition of the present invention is 0.1 to 5 parts by mass, preferably 0.5 to 3 parts by mass, relative to 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition. If the content of the component (d) is less than 0.1 parts by mass, the strength of the cured product and the molded body obtained from the imprint photocurable composition may be reduced, and if it is more than 5 parts by mass, the heat yellowing resistance of the cured product and the molded body may be deteriorated.

[0065] The photoradical initiator of the component (d) may be used alone or in combination of two or more.

[0066] [Component (e): a polyfunctional (meth)acrylate compound having an ethylenically unsaturated group and not containing an aromatic ring]

[0067] The polyfunctional (meth)acrylate compound containing no aromatic ring that can be used as the (e) component of the imprint photocurable composition of the present invention is a compound containing no aromatic ring other than the polyrotaxane as the (c) component and the urethane (meth)acrylate compound or epoxy (meth)acrylate compound as the (f) component described later, which has at least two (meth)acryloyloxy groups in one molecule of the compound. The aromatic ring here includes a carbon ring or a heterocyclic ring that satisfies the Huckel rule, for example, benzene, naphthalene, azulene, anthracene, tetracene, pentacene, phenanthrene, pyrene, furan, thiophene, pyrrole, pyrazole, imidazole, azole, thiazole, pyridine, pyridazine, pyrimidine, pyrazine and triazine. Therefore, the so-called non-aromatic ring means that it does not contain a carbon ring or a heterocyclic ring that satisfies the Huckel rule. Examples of the polyfunctional (meth)acrylate compound that does not contain an aromatic ring include ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, ethoxylated glycerol tri(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, polyglycerol monoethylene oxide poly(meth)acrylate, dipentaerythritol hexa(meth)acrylate, neopentyl glycol di(meth)acrylate, and polyoxyethylene glycol di(meth)acrylate. alcohol di(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, 1,3-adamantanediol di(meth)acrylate, 1,4-cyclohexanedimethanol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and tri(2-acryloyloxyethyl)isocyanurate.

[0068] As the polyfunctional (meth)acrylate compound not containing an aromatic ring, commercially available products can be used, for example, NK Aster A-200, NK Aster A-400, NK Aster A-600, NK Aster A-1000, NK Aster A-9300, NK Aster A-9300-1CL, NK NKエステル1G, NKエステル2G, NKエステル3G, NKエステル4G, NKエステル9G, NKエステル14G, NKエステル23 G、NKエステルA-GLY-3E、NKエステルA-GLY-9E、NKエステルA-GLY-20E、NKエステルA-TMPT- 3EO, NKエステルA-TMPT-9EO, NKエステルATM-4E, NKエステルATM-35E, NKエステルA-DPH, N KエステルA-TMPT, NKエステルA-DCP, NKエステルA-HD-N, NKエステルA-NOD-N, NKエステルAD-T MP、NKエステルA-DOG、NKエステルTMPT、NKエステルDCP、NKエステルNPG、NKエステルHD-N、NKエスTetraNOD-N, NKエステルD-TMP (above, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), KAYARAD (registered trademark) DPHA, KAYARAD NPGDA, KAYARAD PET30, KAYARAD DPEA-12, KAYARAD PEG400DA, KAYARAD RP-1040 (above, manufactured by Nippon Kayaku Co., Ltd.), M-210, M-350 (above, manufactured by Toagosei Co., Ltd.).

[0069] When the imprint photocurable composition of the present invention contains component (e), the content thereof is 5 to 50 parts by mass, preferably 5 to 30 parts by mass, relative to 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition. If the content of component (e) is less than 5 parts by mass, the crosslinking density of the cured product and the molded body obtained from the imprint photocurable composition is reduced, and the shape of the cured product and the molded body is deformed during heat treatment. If the content of component (e) is more than 50 parts by mass, the effect of reducing the birefringence of the cured product and the molded body may become insufficient.

[0070] The polyfunctional (meth)acrylate compound not containing an aromatic ring as the component (e) may be used alone or in combination of two or more.

[0071] [Component (f): urethane (meth)acrylate compound or epoxy (meth)acrylate compound having an ethylenically unsaturated group]

[0072] The urethane (meth)acrylate compound that can be used as the component (f) of the imprint photocurable composition of the present invention is a compound having at least two (meth)acryloyloxy groups and at least two urethane structures represented by "-NH-C(=O)O-" in one molecule. Examples of the urethane (meth)acrylate compound include EBECRYL (registered trademark) 230, EBECRYL 270, EBECRYL 280 / 15IB, EBECRYL 284, EBECRYL 4491, EBECRYL 4683, EBECRYL 4858, EBECRYL 8307, EBECRYL 8402, EBECRYL 8411, EBECRYL8804, EBECRYL 8807, EBECRYL 9270, EBECRYL 8800, EBECRYL 294 / 25HD, EBECRYL 4100, EBECRYL 4220, EBECRYL 4513, EBECRYL 4738, EBECRYL 4740, EBECRYL 4820, EBECRYL 8311, EBECRYL 8465, EBECRYL 9260, EBECRYL 8701, KRM7735, KRM 8667, KRM 8296 (all manufactured by Daicel Olex Co., Ltd.), UV-2000B, UV-2750B, UV-3000B, UV-3200B, UV-3210EA, UV-3300B, UV-3310B, UV-3500B, UV-3520EA, UV-3700B, UV-6640B, UV-6630B, UV-7000B, UV-7510B, UV-7461TE (all manufactured by Nippon Synthetic Chemical Co., Ltd.), UA-306H, UA-306T, UA-306I, UA-5 10H, UF-8001G (above, manufactured by Kyeisha Chemical Co., Ltd.), M-1100, M-1200 (above, manufactured by Toagosei Co., Ltd.), and NKオリゴU-2PPA, NKオリゴU-6LPA, NKオリゴU-200PA, U-200PA, NKオリゴU-160TM, NKオリゴU-290TM, NKオリゴUA-4200, NKオリゴUA-4400, NKオリゴUA-122P, NKオリゴUA-7100, NKオリゴUA-W2A (the above, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.).

[0073] The epoxy (meth)acrylate compound that can be used as the component (f) of the imprint photocurable composition of the present invention is an ester obtained by reacting a compound having at least two epoxy rings in one molecule with (meth)acrylic acid. Examples of the epoxy (meth)acrylate compound include EBECRYL (registered trademark) 645, EBECRYL 648, EBECRYL 860, EBECRYL 3500, EBECRYL 3608, EBECRYL 3702, EBECRYL 3708 (above, manufactured by Nasukuro Aromatic Co., Ltd.), DA-911M, DA-920, DA-931, DA-314, DA-212 (above, manufactured by Nostalgia Co., Ltd.), HPEA-100 (manufactured by Kebab Electronics Co., Ltd.), and Helicopter Co., Ltd. (registered trademark) V-550 0. Divination V-5502, Divination V-5508 (the above, manufactured by DIC Co., Ltd.).

[0074] As the urethane (meth)acrylate compound or epoxy (meth)acrylate compound of the component (f), it is preferable to use a compound having two or three (meth)acryloyloxy groups in one molecule of the compound.

[0075] When the imprint photocurable composition of the present invention contains component (f), the content thereof is 5 to 50 parts by mass, preferably 5 to 30 parts by mass, relative to 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition. If the content of component (f) is less than 5 parts by mass, the cured product and molded body obtained from the imprint photocurable composition may become brittle, thereby reducing the crack resistance of the cured product and molded body when heated. If the content is more than 50 parts by mass, the shape change of the cured product and molded body when heated may increase due to the reduction of the crosslinking density.

[0076] The urethane (meth)acrylate compound or epoxy (meth)acrylate compound of the component (f) may be used alone or in combination of two or more.

[0077] [(g) Ingredient: phenolic antioxidant]

[0078] Examples of the phenolic antioxidant that can be used as the component (g) of the photocurable composition for imprint of the present invention include IRGANOX (registered trademark) 245, IRGANOX 1010, IRGANOX 1035, IRGANOX 1076, and IRGANOX 1135 (all manufactured by BASF Japan Co., Ltd.), SUMILIZER (registered trademark) GA-80, SUMILIZER GP, SUMILIZER MDP-S, SUMILIZER BBM-S, and SUMILIZER WX-R (above, manufactured by Sumitomo Chemical Co., Ltd.), and アデカスタブ(registered trademark) AO-20, アデカスタブAO-30, アデカスタブAO-40, アAdequate AO-50, Adequate AO-60, Adequate AO-80, Adequate AO-330 (above, manufactured by ADEKA Co., Ltd.).

[0079] When the imprint photocurable composition of the present invention contains the component (g), the content thereof is 0.05 to 3 parts by mass, preferably 0.1 to 1 part by mass, based on 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group.

[0080] The phenolic antioxidant as the component (g) may be used alone or in combination of two or more.

[0081] [Component (h): thioether antioxidant]

[0082] Examples of the thioether antioxidant that can be used as the component (h) of the photocurable composition for imprint of the present invention include ADEKA STABU (registered trademark) AO-412S, ADEKA STABU AO-503 (each manufactured by ADEKA Corporation), IRGANOX (registered trademark) PS802, IRGANOX PS800 (each manufactured by BASF), and SUMILIZER (registered trademark) TP-D (manufactured by Sumitomo Chemical Co., Ltd.).

[0083] When the imprint photocurable composition of the present invention contains the component (h), the content thereof is 0.1 to 3 parts by mass, preferably 0.1 to 1 part by mass, based on 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition.

[0084] The thioether antioxidant as the component (h) may be used alone or in combination of two or more.

[0085] <Other additives>

[0086] Furthermore, the imprint photocurable composition of the present invention may contain a chain transfer agent, an antioxidant, an ultraviolet absorber, a light stabilizer, a leveling agent, a rheology regulator, an adhesion promoter such as a silane coupling agent, a pigment, a dye, a defoaming agent, etc. as needed, unless the effects of the present invention are impaired.

[0087] <Method for preparing photocurable composition for imprint>

[0088] The method for preparing the imprint photocurable composition of the present invention is not particularly limited. As a preparation method, for example, there can be mentioned a method of mixing the components (a), (b), (c), and (d), and as required, the components (e) and / or (f), (g), and / or (h) in a predetermined ratio to prepare a uniform solution.

[0089] The photocurable composition for imprint of the present invention prepared as a solution is preferably filtered using a filter having a pore size of 0.1 μm to 5 μm or the like before use.

[0090] <Cured product>

[0091] The photocurable composition for imprinting of the present invention can be exposed (photocured) to obtain a cured product, and the present invention also takes the cured product as an object. As the light for exposure, for example, ultraviolet rays, electron beams and X-rays can be cited. As the light source used for ultraviolet irradiation, for example, sunlight, chemical lamps, low-pressure mercury lamps, high-pressure mercury lamps, metal halide lamps, xenon lamps, and UV-LEDs can be used. In addition, after exposure, in order to stabilize the physical properties of the cured product, post-baking can be implemented. There is no particular limitation on the method of post-baking. Generally, a hot plate, an oven, etc. are used at 50°C to 260°C and 1 minute to 24 hours.

[0092] The Abbe number v of the cured product obtained by photocuring the photocurable composition for imprint of the present invention is D The refractive index n is as high as 53 or more at a wavelength of 589nm (D line). D The photocurable composition for imprint of the present invention is preferably used for forming a resin lens.

[0093] <Molding body>

[0094] The imprint photocurable composition of the present invention can be used, for example, by using an imprint molding method, so that various molded bodies can be easily manufactured simultaneously with the formation of a cured product. As a method for manufacturing a molded body, for example, the following method can be cited, which includes the following steps: a step of filling the imprint photocurable composition of the present invention in the space between the support and the mold in contact with each other, or the internal space of the detachable mold; a step of exposing the imprint photocurable composition filled in the space to photocuring; a step of taking out the photocured material obtained by the photocuring step and demolding; and a step of heating the photocured material before, during or after the demolding step. At this time, after the step of taking out the photocured material obtained by the above-mentioned photocuring step and demolding, before the above-mentioned heating step, a developing step of washing / removing the uncured part with an organic solvent may be further included. As a method for making the above-mentioned uncured part, there is no particular restriction, and only a specified position is exposed by mask exposure, projection exposure, etc., so that the unexposed part, that is, the uncured part, can be made. Furthermore, the photocured material after the development step may be exposed again to light and cured as necessary.

[0095] The above-mentioned exposure and photocuring process can be implemented by applying the conditions for obtaining the above-mentioned cured product. Further, the conditions for the process of heating the above-mentioned photocured product are not particularly limited, but are generally appropriately selected from the range of 50°C to 260°C and 1 minute to 24 hours. In addition, as a heating means, there is no particular limitation, and examples include a hot plate and an oven. The molded body manufactured by such a method can be suitably used as a lens for a camera module.

[0096] Example

[0097] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In the following examples and comparative examples, the apparatuses and conditions used for sample preparation and property analysis are as follows.

[0098] (1) Mixing and degassing machine

[0099] Equipment: Rotation / revolution mixer Awatori Rentaro (registered trademark) ARE-310 manufactured by Shinki Co., Ltd.

[0100] (2) UV exposure

[0101] Device: Intermittent UV-LED irradiation device manufactured by Seashell Co., Ltd. (wavelength 365nm)

[0102] (3) Refractive index n D , Abbe number ν D

[0103] Device: Abbemat MW, a multi-wavelength refractometer manufactured by アントンパール Co., Ltd.

[0104] Measurement temperature: 23°C

[0105] (4) Birefringence measurement

[0106] Device: WPA-100 manufactured by Furutech Co., Ltd.

[0107] Conditions: Wavelength = 543nm, Temperature = Room Temperature

[0108] (5) Digital Microscope (Evaluation of Crack Resistance in Development Process Using Organic Solvents)

[0109] Device: KH-7700, MXG-2500REZ manufactured by Hakko Co., Ltd.

[0110] Conditions: Reflection (dark field), Low-Range, 100x

[0111] (6) Formation of anti-reflection layer

[0112] Equipment: SRV4300 series manufactured by Shinko Seiki Co., Ltd.

[0113] Method: RF sputtering / magnetron method

[0114] Conditions: target material = SiO2, vertical distance between target and substrate = 100 mm,

[0115] Temperature = room temperature, sputtering time = 29 minutes

[0116] (7) Optical microscope (observation of anti-reflection film)

[0117] Device: (VHX-1000, VH-Z1000R manufactured by Konosu Co., Ltd.

[0118] Conditions: reflection (bright field), objective lens 500 times

[0119] (8) Lens molding

[0120] Device: 6-inch compatible nano printer manufactured by Myeongchang Machinery Co., Ltd.

[0121] Light source: Exposure via a high-pressure mercury lamp and i-ray bandpass filter HB0365 (manufactured by Asahi Spectroscopy Co., Ltd.)

[0122] Molding conditions: Pressing pressure 100N, 20mW / cm 2 ×300 seconds

[0123] (9) Lens height measurement

[0124] Device: Non-contact surface property measuring device PF-60 manufactured by Mitaka Koki Co., Ltd.

[0125] The suppliers of the compounds used in each Production Example, Example and Comparative Example are as follows.

[0126] A-DCP: manufactured by Shin-Nakamura Chemical Industry Co., Ltd. Trade name: NK Esther A-DCP

[0127] MEK-AC-2140Z: Made by Nissan Chemical Industries, Ltd. Trade name: Olgano Silicone Sol MEK-AC-2140Z

[0128] FA-513AS: Manufactured by Hitachi Chemical Co., Ltd. Trade name: FA-513AS (registered trademark)

[0129] FA-512AS: Made by Hitachi Chemical Co., Ltd. Trade name: Fancleil (registered trademark) FA-512AS

[0130] SA1303P: Manufactured by アドバンスト・ソフトマテリアルズ Co., Ltd. Trade name: セルム (registered trademark) スーパーポリマーSA1303P

[0131] IBA: Osaka Organic Chemical Industry Co., Ltd. Trade name: IBXA

[0132] UA-4200: Made by Shin-Nakamura Chemical Industry Co., Ltd. Trade name: NK Olig UA-4200

[0133] I184: Made by BASF Trade name: Irgacure (registered trademark) 184

[0134] I245: Made by BASF Trade name: Irganox (registered trademark) 245

[0135] AO-503: Made by ADEKA Co., Ltd. Trade name: ADEKA STABU (registered trademark) AO-503

[0136] [Production Example 1]

[0137] 200 g of A-DCP as (e) the above-mentioned multifunctional (meth)acrylate compound not containing an aromatic ring was weighed in a 500 mL eggplant flask and dissolved in 200 g of methyl ethyl ketone (hereinafter referred to as MEK in this specification). Then, as (a) the above-mentioned silica particles surface-modified with functional groups having ethylenically unsaturated groups, 441 g of MEK-AC-2140Z (silica particles with a primary particle size of 10 nm to 15 nm surface-modified with (meth)acryloyloxy groups, a MEK dispersion with a solid content of 45% by mass) was added and stirred for homogenization. Then, using an evaporator, MEK was distilled off at 50° C. and a reduced pressure of less than 133.3 Pa to obtain the A-DCP dispersion of the above-mentioned silica particles surface-modified with functional groups having ethylenically unsaturated groups (the surface-modified silica particles contain 50% by mass).

[0138] [Production Example 2]

[0139] 100 g of FA-513AS as (b) monofunctional (meth)acrylate compound was weighed in a 500 mL eggplant flask and dissolved in 100 g of MEK. Then, 222 g of MEK-AC-2140Z (silica particles with a primary particle size of 10 nm to 15 nm surface-modified by (meth)acryloyloxy groups, a MEK dispersion with a solid content of 45% by mass) was added as (a) the above-mentioned silica particles surface-modified by functional groups having ethylenic unsaturated groups, and stirred to make them uniform. Then, using an evaporator, MEK was distilled off at 50° C. and a reduced pressure of 133.3 Pa or less, to obtain the FA-513AS dispersion of silica particles surface-modified by functional groups having ethylenic unsaturated groups (the surface-modified silica particles contain 50% by mass).

[0140] [Production Example 3]

[0141] UA-420050.0g as (f) urethane (meth) acrylate compound was weighed in a 500mL eggplant flask and dissolved in MEK 50.0g. Then, as (a) the above-mentioned silica particles surface-modified with functional groups having ethylenically unsaturated groups, MEK-AC-2140Z (silica particles with a primary particle size of 10nm to 15nm surface-modified with (meth) acryloyloxy groups, MEK dispersion with a solid content of 45% by mass) 111g was added and stirred to make uniform. Then, MEK was distilled off at 60°C and a reduced pressure of 133.3Pa or less using an evaporator to obtain the UA-4200 dispersion of silica particles surface-modified with functional groups having ethylenically unsaturated groups (the surface-modified silica particles contain 50% by mass).

[0142] [Production Example 4]

[0143] 20.0 g of A-DCP, which is the polyfunctional (meth)acrylate compound having an ethylenically unsaturated group and not containing an aromatic ring, was weighed in a 500 mL eggplant flask. Then, 40.0 g of SA1303P (a polyrotaxane having an acryloyl group in the side chain of a cyclic molecule formed by cyclodextrin, a MEK dispersion having a solid content of 50% by mass) was added as the polyrotaxane having an ethylenically unsaturated group (c), and the mixture was stirred and homogenized. Then, MEK was distilled off using an evaporator at 50° C. and a reduced pressure of 133.3 Pa or less, to obtain an A-DCP solution of the polyrotaxane having an ethylenically unsaturated group (the polyrotaxane having an ethylenically unsaturated group contains 50% by mass).

[0144] [Example 1]

[0145] The solid content of the A-DCP dispersion obtained in Production Example 1 as (a) silica particles surface-modified with a functional group having an ethylenically unsaturated group, the solid content of the FA-513AS dispersion obtained in Production Example 2, FA-513AS as (b) a monofunctional (meth)acrylate compound having an ethylenically unsaturated group, the solid content of the A-DCP solution obtained in Production Example 4 as (c) a polyrotaxane having an ethylenically unsaturated group, I184 as (d) a photoradical initiator, A-DCP as (e) a polyfunctional (meth)acrylate compound having an ethylenically unsaturated group and not containing an aromatic ring, UA-4200 as (f) a urethane (meth)acrylate compound having an ethylenically unsaturated group, I245 as (g) a phenolic antioxidant, and AO-503 as (h) a thioether antioxidant were blended in the ratios shown in Table 1 below. In addition, the ratio of A-DCP shown in the following Table 1 includes the A-DCP component contained in the above-mentioned A-DCP dispersion and the above-mentioned A-DCP solution, and the ratio of FA-513AS includes the FA-513AS contained in the above-mentioned FA-513AS dispersion. Then, the mixture was shaken at 50° C. for 16 hours and stirred and degassed for 10 minutes using the above-mentioned stirring degassing machine to prepare the imprint photocurable composition 1. In addition, in the following Table 1, "parts" means "parts by mass".

[0146] [Example 2 to Example 5, Comparative Example 1]

[0147] By the same procedure as in Example 1, components (a) to (h) were mixed in the ratios shown in Table 1 below to prepare imprint photocurable compositions 2 to 6. However, in Comparative Example 1, components (b) and (c) were not used.

[0148]

[0149] [Preparation of Cured Film]

[0150] Each imprint photocurable composition prepared in Examples 1 to 5 and Comparative Example 1 was sandwiched between two glass substrates that had been subjected to a mold release treatment by coating and drying with NOVEC (registered trademark) 1720 (manufactured by SLIEM Japan Co., Ltd.). The sandwiched imprint photocurable composition was irradiated with the above-mentioned UV-LED irradiation device at 30 mW / cm 2 The UV exposure was performed for 200 seconds. The cured product obtained after the exposure was peeled off from the glass substrate subjected to the mold release treatment, and then heated on a hot plate at 100° C. for 10 minutes to produce a cured film having a diameter of 1 cm and a thickness of 0.5 mm.

[0151] [Refractive index n D / Abbe number ν D evaluate]

[0152] The refractive index n of the cured film produced by the above method at a wavelength of 589 nm was measured using the above multi-wavelength refractometer. D , and the Abbe number ν D The results are shown together in Table 2 below.

[0153] [Evaluation of Crack Resistance of Cured Film in Development Process Using Organic Solvent]

[0154] An appropriate amount of each imprint photocurable composition prepared in Examples 1 to 5 and Comparative Example 1 is dropped onto a photomask substrate (opening 1 cm square) that has been subjected to a demolding treatment by coating with NOVEC (registered trademark) 1720 (manufactured by Sliem Japan Co., Ltd.) and drying. Then, the imprint photocurable composition on the photomask substrate subjected to the above demolding treatment is sandwiched between 4-inch glass wafers (0.7 mm thick) via a 500 μm thick silicone rubber spacer. The 4-inch glass wafer is subjected to a sealing treatment by coating a 30% by mass solution of propylene glycol monomethyl ether acetate (hereinafter referred to as PGMEA in this specification) diluted with an adhesive aid (product name: KBM-5103) manufactured by Shin-Etsu Chemical Co., Ltd. and drying. The sandwiched photocurable composition is irradiated with light at 115 mW / cm 2UV exposure was performed for 2.2 seconds. After exposure, the obtained cured product was peeled off from the above-mentioned demolding photomask substrate, immersed in stirred PGMEA (development), and further rinsed with PGMEA to remove the unexposed portion, thereby preparing a 1 cm square, 0.5 mm thick cured film on the above-mentioned 4-inch glass wafer that was subjected to a close bonding treatment. The obtained cured film was observed using the digital microscope made by Hilox, and the situation where cracks were confirmed was judged as ×, and the situation where cracks were not observed was judged as ○. The results are shown together in Table 2 below.

[0155] [Measurement of Birefringence of Cured Film]

[0156] 0.030 g of each imprint photocurable composition prepared in Examples 1 to 5 and Comparative Example 1 was weighed on a glass substrate that had been subjected to a demolding treatment by coating with NOVEC (registered trademark) 1720 (manufactured by Slider Emery Co., Ltd.) and drying. Then, the imprint photocurable composition on the demolding glass substrate was sandwiched between quartz substrates (4 cm square, 1 mm thick) via a 500 μm thick silicone rubber spacer. The quartz substrate was subjected to a sealing treatment by coating with a solution of a 30% by mass solution of an adhesive auxiliary agent (product name: KBM-5103) manufactured by Shin-Etsu Chemical Co., Ltd. diluted with PGMEA and dried. The sandwiched photocurable composition was irradiated with 30 mW / cm 2 UV exposure was performed for 200 seconds. After exposure, the obtained cured product was peeled off from the above-mentioned demolding glass substrate and heated on a 100°C hot plate for 10 minutes to produce a cured film with a diameter of 1 cm, a thickness of 0.5 mm and a mass of 0.030 g on the above-mentioned quartz substrate subjected to the sealing treatment. The obtained cured film was measured for the phase difference in the cured film using the above-mentioned phase difference measuring device manufactured by Fotonic Latex. The maximum phase difference in the cured film (wherein the portion approximately 1 mm from the periphery produces a phase difference caused by the cross-sectional structure and is therefore excluded from the analysis) was divided by the film thickness of the cured product, 0.5 mm, to calculate the birefringence of each cured product. The birefringence was calculated by taking 2.5×10 -5 The following cases are judged as ○, which is higher than 2.5×10 -5 The results are shown in Table 2 below.

[0157] [Film formation of anti-reflection layer (AR layer) and evaluation of its crack resistance]

[0158] 0.017 g of each imprint photocurable composition prepared in Examples 1, 2 and 4 and Comparative Example 1 was weighed on a glass substrate that had been subjected to a demolding treatment by coating with NOVEC (registered trademark) 1720 (manufactured by Sliem Japan Co., Ltd.) and drying. Then, the imprint photocurable composition on the demolding glass substrate was sandwiched with a quartz substrate (6 cm square, 1 mm thick) via a 300 μm thick silicone rubber spacer. The quartz substrate was subjected to a sealing treatment by coating with a solution of a 30% by mass solution of an adhesive additive (product name: KBM-5103) manufactured by Shin-Etsu Chemical Co., Ltd. diluted with PGMEA and dried. The sandwiched photocurable composition was irradiated with 30 mW / cm 2 The UV exposure was performed for 200 seconds. After exposure, the obtained cured product was peeled off from the glass substrate subjected to the demolding treatment and heated on a hot plate at 100° C. for 10 minutes, thereby forming a cured film with a diameter of 1 cm, a thickness of 0.3 mm and a mass of 0.017 g on the quartz substrate.

[0159] On the cured film produced on the above-mentioned quartz substrate, a silicon oxide layer with a film thickness of 200 nm was formed as an anti-reflection layer using the above-mentioned RF sputtering device under the above-mentioned film forming conditions. After observing the anti-reflection layer on the above-mentioned cured film using the above-mentioned Keyence optical microscope to confirm the presence or absence of cracks, the above-mentioned quartz substrate was heated on a hot plate at 175°C for 2 minutes and 30 seconds to conduct a heat resistance test. Regarding the above-mentioned quartz substrate after the heat resistance test, the presence or absence of cracks in the anti-reflection layer on the above-mentioned cured film was also observed using the above-mentioned Keyence optical microscope to determine the crack resistance of the anti-reflection layer. The case where cracks can be identified in the anti-reflection layer on the above-mentioned cured film is judged as ×, and the case where neither cracks nor wrinkles can be identified in the anti-reflection layer on the cured film is judged as ○. The respective results are shown together in the following Table 2.

[0160] Table 2

[0161]

[0162] The cured film produced from the imprint photocurable composition of Comparative Example 1 not containing the components (b) and (c) resulted in cracks on the side of the cured film after the development step using an organic solvent, and the birefringence of the cured product was also high. The above results show that the cured film obtained from the imprint photocurable composition of the present invention has high Abbe number, high refractive index, low birefringence, and the antireflection layer having the upper layer of the cured film does not crack or wrinkle after heat treatment at 175°C, and does not crack even when exposed to an organic solvent, which are desirable characteristics for a lens for a high-resolution camera module.

[0163] [Lens production]

[0164] Each imprint photocurable composition prepared in Examples 1, 2 and 4 was molded into a lens shape on a quartz substrate as a support according to the above-mentioned method for manufacturing a molded body using a nickel mold (a lens mold with a diameter of 2 mm and a depth of 300 μm is arranged in 3 vertical rows and 5 horizontal rows, totaling 15) and a nano printer. In addition, the mold used was previously subjected to a demolding treatment using NOVEC (registered trademark) 1720 (manufactured by Sly-Em Diaman Co., Ltd.). In addition, the glass substrate used was previously subjected to a sealing treatment by coating a bonding aid (product name: KBM-5103) manufactured by Shin-Etsu Chemical Co., Ltd. with a solution diluted to 30% by mass with PGMEA and then drying it. After removing the cured product from the above-mentioned mold, the cured product was heated on a 100°C hot plate for 10 minutes to produce a convex lens on the above-mentioned glass substrate subjected to the sealing treatment.

[0165] Regarding the convex lens obtained on the above-mentioned glass substrate, the lens height (thickness) before and after the heating test was measured using the above-mentioned non-contact surface property measuring device, and the rate of change was calculated by the following formula "[(lens height before heating - lens height after heating) / lens height before heating] × 100", and the dimensional stability based on heating was evaluated. In addition, the presence of cracks in the convex lens after the heating test was observed using a microscope attached to the above-mentioned non-contact surface property measuring device. In addition, the so-called heating test is a test in which the convex lens obtained on the glass substrate is heated on a 175°C hot plate for 2 minutes and 30 seconds and then cooled to room temperature (about 23°C). The results are shown in Table 3 below.

[0166] Table 3

[0167]

[0168] As shown in Table 3, the convex lens obtained from the imprint photocurable composition of the present invention showed a small change in lens height (change rate less than 0.30%) even after a thermal history of 175°C for 2 minutes and 30 seconds, and had high dimensional stability.

Claims

1. A photocurable composition for imprinting, comprising the following component a, the following component b, the following component c, and the following component d, wherein the component a is 10 to 40 parts by mass, the component b is 10 to 50 parts by mass, the component c is 1 to 10 parts by mass, and the component d is 0.1 to 5 parts by mass, relative to 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition, Component a: silica particles having a primary particle size of 1 to 100 nm and surface-modified with a functional group having an ethylenically unsaturated group, Component b: a monofunctional (meth)acrylate compound having an ethylenically unsaturated group, which is an alicyclic (meth)acrylate compound, Component c: a polyrotaxane having an ethylenically unsaturated group, wherein the cyclic molecule of the polyrotaxane is selected from α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, Component d: Photo radical initiator, Furthermore, the composition further comprises 5 to 50 parts by mass of the following component e and / or the following component f, based on 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition. Component e: a polyfunctional (meth)acrylate compound having an ethylenically unsaturated group and not containing an aromatic ring, wherein: The component e does not include the polyrotaxane as the component c and the urethane (meth)acrylate compound or epoxy (meth)acrylate compound as the component f. Component f: a urethane (meth)acrylate compound or an epoxy (meth)acrylate compound having an ethylenically unsaturated group, wherein component f does not include the polyrotaxane as component c.

2. The photocurable composition for imprint according to claim 1, further comprising 0.05 to 3 parts by mass of the following component g relative to 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition, and / or 0.1 to 3 parts by mass of the following component h relative to 100 parts by mass of the total amount of the compound having an ethylenically unsaturated group contained in the composition, g ingredients: phenolic antioxidants, Component h: thioether antioxidant. 3 . The photocurable composition for imprint according to claim 1 , wherein the component (a) is silica particles surface-modified with (meth)acryloyloxy groups bonded to silicon atoms via divalent linking groups. 4 . The photocurable composition for imprint according to claim 1 , wherein the polyfunctional (meth)acrylate compound not containing an aromatic ring as the component (e) is composed of two or more compounds, and at least one of the two or more compounds has an alicyclic hydrocarbon group.

5. The photocurable composition for imprint according to claim 1 or 2, wherein the refractive index n of a cured product of the photocurable composition for imprint at a wavelength of 589 nm is D is 1.49 or more, and the Abbe number ν of the cured product is D 53 and above. 6 . A cured product, which is a cured product of the photocurable composition for imprint according to claim 5 . 7 . A method for producing a resin lens, comprising the step of imprint-molding the photocurable composition for imprint according to claim 1 .

8. A method for manufacturing a molded body, which is a method for manufacturing a molded body of a photocurable composition for imprinting, comprising the following steps: a step of filling the space between a support and a casting mold that are in contact with each other, or the internal space of a detachable casting mold, with the photocurable composition for imprinting described in any one of claims 1 to 5; and a step of exposing the photocurable composition for imprinting filled in the space to photocuring.

9. The method for manufacturing a molded body according to claim 8, further comprising the following steps: a step of taking out the obtained photocured material and demolding the material after the photocuring step; and a step of heating the photocured material before, during or after the demolding step. 10 . The method for producing a molded product according to claim 9 , further comprising a development step using an organic solvent after the demolding step and before the heating step. 11 . The method for producing a molded article according to claim 8 , wherein the molded article is a lens for a camera module.